DAMPAK PERMAINAN OLAHRAGA TRADISIONAL GOBAK SODOR TERHADAP KEMAMPUAN GERAK KASAR SISWA KELAS V DI SD NEGERI CIGINTUNG - Fauzan Zainal Abidin; Ribut Wahidi (STKIP Subang, 2026)
This study aimed to examine the impact of the traditional sports game gobak sodor on the gross motor skills of fifth-grade students at SD Negeri Cigintung. A quantitative approach with a one-group pretest-posttest design was used. The participants were 20 fifth-grade students selected through total sampling. Gross motor skills were assessed using the Test of Gross Motor Development–Third Edition (TGMD-3), covering locomotor and manipulative skills. The gobak sodor intervention was implemented in 18 sessions over six weeks, three sessions per week. Data were analyzed using Shapiro-Wilk and paired-samples t-test with SPSS. Mean locomotor scores increased from 28.00 to 40.45, while manipulative scores increased from 32.25 to 45.35. The test produced t = 11.714 with p < 0.001, indicating a significant difference after the intervention. Gobak sodor can therefore be used as an engaging, locally grounded physical education activity to support gross motor development